Directorate of Postgraduate Training Strategic Plan - Kabale University (Kabale University, 2022)
To generate a postgraduate education that is efficient, effective and transformative when responding to emerging international, community, stakeholder and citizenship demands over the next five years (2020/21-2024/25)